Loading rates of dust and bioburden in dwellings in an Inland city of Southern Europe - Viegas, Carla (2021)
Sampling campaigns indoors have shown that occupants exposed to contaminated air generally exhibit diverse health outcomes. This study intends to assess the deposition rates of total settleable dust and bioburden in the indoor air of dwellings onto quartz fiber filters and electrostatic dust collectors (EDCs), respectively. EDC extracts were inoculated onto malt extract agar (MEA) and dichloran glycerol (DG18) agar-based media used for fungal contamination characterization, while tryptic soy agar (TSA) was applied for total bacteria assessment, and violet red bile agar (VRBA) for Gram-negative bacteria. Azole-resistance screening and molecular detection by qPCR was also performed. Dust loading rates ranged from 0.111 to 3.52, averaging 0.675 μg cm−2 day−1. Bacterial counts ranged from undetectable to 16.3 colony-forming units (CFU) m−2 day−1 and to 2.95 CFU m−2 day−1 in TSA and VRBA, respectively. Fungal contamination ranged from 1.97 to 35.4 CFU m−2 day−1 in MEA, and from undetectable to 48.8 CFU m−2 day−1 in DG18. Penicillium sp. presented the highest prevalence in MEA media (36.2%) and Cladosporium sp. in DG18 (39.2%). It was possible to observe: (a) settleable dust loadings and fungal contamination higher in dwellings with pets; (b) fungal species considered indicators of harmful fungal contamination; (c) Aspergillus section Candidi identified in supplemented media with voriconazole and posaconazole; (d) specific housing typologies and (e) specific housing characteristics influencing the microbial contamination.